2009
DOI: 10.1094/pdis-93-1-0067
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Viruses Infecting Tomato and Their Natural Hosts in the Southeast and Central Regions of Iran

Abstract: A survey was conducted to determine the incidence of Cucumber mosaic virus (CMV), Beet curly top virus (BCTV), Tomato yellow leaf curl virus (TYLCV), Tomato chlorotic spot virus (TcSV), Potato virus Y (PVY), Potato virus S (PVS), Tomato spotted wilt virus (TSWV), Tomato ringspot virus (TRSV), Tomato aspermy virus (TAV), Arabis mosaic virus (ArMV), Tobacco streak virus (TSV), Tomato bushy stunt virus (TBSV), Tobacco mosaic virus (TMV), and Tomato mosaic virus (ToMV) on tomato (Solanum lycopersicum) in the major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 34 publications
1
29
0
Order By: Relevance
“…; Massumi et al. ). We report here the incidence and sequence analysis of coat protein (CP) derived from Iranian isolates of PSV.…”
Section: Introductionmentioning
confidence: 97%
“…; Massumi et al. ). We report here the incidence and sequence analysis of coat protein (CP) derived from Iranian isolates of PSV.…”
Section: Introductionmentioning
confidence: 97%
“…In July 1998, TSWV was identified from Pittosporum tobira shrubs with foliar ring spots, mild mosaic, and tip necrosis symptoms in a nursery in the Sharon Valley of Israel (Gera et al ., ), and later from several vegetables (Gera et al ., ). Similarly, the virus was also detected from potatoes in 1998 in Iran (Pourrahim et al ., ), and subsequently from soybeans, tomatoes, and cucurbits (Golnaraghi et al ., ; Massumi et al ., , ). TSWV has also been isolated from many important vegetable crops in Jordan and Lebanon (Anfoka et al ., ; Abou‐Jawdah et al ., ).…”
Section: Current Global Status Of the Viruses Transmitted By F Occidmentioning
confidence: 99%
“…Iran is amongst the seven top producers of tomato (Solanum lycopersicum) in the world with an approximate production of 4,826,396 tonnes yearly (Faostat, 2009) (Massumi et al, 2009). However, Tobacco mild green mosaic virus (TMGMV), already reported in pepper in Asia (Choi et al, 2002;Li & Chang, 2005) has not been identified in Iran yet.…”
Section: Figure 1 Figurementioning
confidence: 99%